2011
DOI: 10.1145/2043662.2043671
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Spilling Reduction for Software Pipelined Loops in Presence of Multiple Register Types in Embedded VLIW Processors

Abstract: SID-AHMED-ALI TOUATI, University of Versailles Saint-Quentin-en-Yvelines FREDERIC BRAULT, INRIA-Saclay KARINE DESCHINKEL, University of Versailles Saint-Quentin-en-Yvelines BENOÎT DUPONT DE DINECHIN, STMicroelectronicsIntegrating register allocation and software pipelining of loops is an active research area. We focus on techniques that precondition the dependence graph before software pipelining in order to ensure that no register spill instructions are inserted by the register allocator in the software pipel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…They are used inside a framework called SIRA [23,24]. Unlike the previous approaches for periodic register allocation, reuse graphs are used before software pipelining to generate a move-free or a spill-free periodic register allocation in the presence of multiple register types.…”
Section: Sira and Reuse Graphsmentioning
confidence: 99%
See 4 more Smart Citations
“…They are used inside a framework called SIRA [23,24]. Unlike the previous approaches for periodic register allocation, reuse graphs are used before software pipelining to generate a move-free or a spill-free periodic register allocation in the presence of multiple register types.…”
Section: Sira and Reuse Graphsmentioning
confidence: 99%
“…A simple way to explain SIRA is to provide an example. All the theory has already been presented in Touati and Eisenbeis [24], and we recently showed that optimising the register requirement for multiple register types in one go is a better approach than optimising for every register type separately [23]. Figure 5(a) provides an initial DDG with two register types t 1 and t 2 .…”
Section: Sira and Reuse Graphsmentioning
confidence: 99%
See 3 more Smart Citations